N-terminomics profiling of host proteins targeted by excretory-secretory proteases of the nematode Angiostrongylus vasorum identifies points of interaction with canine coagulation and complement cascade - Nina Germitsch; Tobias Kockmann; Manuela Schnyder; Lucienne Tritten (PLoS ONE, 2025)
The cardiopulmonary nematode Angiostrongylus vasorum can cause severe disease in dogs, including coagulopathies manifesting with bleeding. We analysed A. vasorum excretory/secretory protein (ESP)-treated dog plasma and serum by N-terminome analysis using Terminal Amine Isotopic Labelling of Substrates (TAILS) to identify cleaved host substrates. In plasma and serum samples 430 and 475 dog proteins were identified, respectively. A total of eight dog proteins were significantly cleaved at higher levels upon exposure to A. vasorum ESP: of these, three were coagulation factors (factor II, V and IX) and three were complement proteins (complement C3, C4-A and C5). Comparison with human motif sequence orthologues revealed known cleavage sites in coagulation factor IX and II (prothrombin). These and further identified cleavage sites suggest direct or indirect activation or proteolysis of complement and coagulation components through A. vasorum ESP, which contains several proteases. Further studies are needed to validate their substrate specificity.